Kinerja ESG: Kontribusi Board Gender Diversity Dan Network - zaitul; Ilona, Desi; Aqila, Foja Ayu Rafifa; Rahmawati, Dessy; Salfadri (Politeknik Caltex Riau, 2023)
Environmental, social and governance (ESG) performance has been a hot topic among investors, decision-makers and academics. Factor affecting ESG performance has been largely done but failed to pay attention to the different board governance systems, such as Indonesia’s board governance system. This paper investigates the contribution of the board gender diversity and board network as well as foreign ownership on ESG performance using blue chip stock (LQ-45) listed in the Indonesia Stock exchange. Seventeen companies with five years of data (2013-2017) participated in this study. Multiple regression analysis is employed, and the result shows that gender diversity on the supervisory board negatively impacts environmental and social performance. Second, the board network on the supervisory board has a positive impact on environmental and social performance, and the board network on the management board has a positive impact on social performance. Third, foreign ownership has a positive effect on governance performance. This research has practical implications where if a company plans to improve ESG performance, it must more effectively select a female supervisory board so that its existence positively impacts ESG performance. In addition, ESG performance can also be increased by appointing a supervisory board who have a high social and professional network so that it can have an impact on ESG performance. Finally, ESG performance can also be improved by increasing foreign ownership. This research contributes to social capital, stakeholder, agency, and resources-dependent theory.